Le silence des choux : délégation de la parole végétale chez Cyrano de Bergerac - Mangili, Adrien (Studia Romanica Posnaniensia, 2025)
Cyrano de Bergerac’s comic narratives provocatively grant speech to animals and plants, radically decentering anthropocentric perspectives. While animal enunciation has been extensively studied, vegetal discourse in Cyrano’s works remains underexplored. This article focuses on the Demon of Socrates’ encomium praising the intellectual superiority of cabbages in the Lune. Beyond its materialist subversion, the speech act raises ethical concerns about appropriating and translating vegetal silence. Though fiction allows cabbages a voice, their muteness persists, foregrounding the incommensurability between human and plant communication. Cyrano’s burlesque world paradoxically highlights the violence inherent in ventriloquizing mute beings.